Beluga Coal Gasification - ISER - Colt, Steve (University of Alaska, 2008)
ISER was requested to conduct an economic analysis of a possible 'Cook Inlet Syngas Pipeline'. The economic analysis was incorporated as section 7.4 of the larger report titled: 'Beluga Coal Gasification Feasibility Study, DOE/NETL-2006/1248, Phase 2 Final Report, October 2006, for Subtask 41817.333.01.01'. The pipeline would carry COsub 2 and Nsub 2-Hsub 2 from a synthetic gas plant on the western side of Cook Inlet to Agrium's facility. The economic analysis determined that the net present value of the total capital and operating lifecycle costs for the pipeline ranges from $318 to $588 million. The greatest contributor to this spread is the cost of electricity, which ranges from $0.05 to $0.10/kWh in this analysis. The financial analysis shows that the delivery cost of gas may range from $0.33 to $0.55/Mcf in the first year depending primarily on the price for electricity.